Gender Responsiveness: The Municipality of San Mateo Case - Leal, R C; Saguibo, O S (KnE Social Sciences, 2018)
This study assessed the level of responsiveness of the Municipality of San Mateo. Descriptive statistics was employed particularly mean in order to obtain the ratings with regard to the level of gender responsiveness. Frequency counts and percentages were also used in determining the profile of LGU San Mateo. It was found out that the socio-economic data of LGU San Mateo provide information in relation to gender-responsiveness and the LGU has the capacity to deliver and employ gender responsive services which were manifested in its systematic approach and moving towards advanced stages of being gender-responsive. Moreover, mechanisms and strategies could be adopted to facilitate the localization of GAD mainstreaming. Keywords: basic services, gender, gender responsiveness